The theory of René Girard: a very simple introduction - Osborn, Carly (Australian Girard Seminar, 2016)
This book is a brief introduction to the theory of René Girard, written in a humorous, accessible style, and accompanied by cartoon illustrations by the author. René Girard (1923-2015) was a French historian, literary critic, and philosopher of social science, whose work belongs to the tradition of anthropological philosophy. His theories and work have influenced the fields of literary criticism, critical theory, anthropology, theology, psychology, mythology, sociology, economics, cultural studies, and philosophy. Girard's fundamental ideas were that desire is imitative in origin ('mimetic'); that mimetic desire causes rivalry and violence, leading to scapegoating; that the scapegoat mechanism is the origin of sacrifice and ritual, and thus the foundation of human culture; that religion developed from ritual; and that the Judeo-Christian Bible denounces the scapegoat mechanism. If you'd like to understand the basics of the theory of René Girard without delving into a serious academic text, then this book was written for you. It also has knights in armour, Batman, Greek tragedy, and hats